(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
To study the effect of glycemic control on the development of diastolic dysfunction and remodeling of the left ventricle in patients with type 2 diabetes mellitus (DM) with the absence or presence of concomitant arterial hypertension.